2020
DOI: 10.1364/ao.388578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photoinitiator concentration on hygroscopic stability of UV cured precision replicated composite optics

Abstract: Replicated composite optics is a promising technique to fabricate high-quality mirrors with reduced weight and processing time compared to conventional glass mirrors; however, the optical layer is organic and susceptible to environmentally-induced dimensional changes, specifically to moisture exposures. Generally, to enhance polymer stability, thermal curing is necessary to maximize the cure state. Because replications are bonded, thermal exposures generate residual stresses that degrade optical quality. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Even though the mechanical properties may still be acceptable for many structural applications, this distortion can negatively impact high-dimensional stability composite applications where nanometer resolutions are critical. 6,7…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the mechanical properties may still be acceptable for many structural applications, this distortion can negatively impact high-dimensional stability composite applications where nanometer resolutions are critical. 6,7…”
Section: Resultsmentioning
confidence: 99%
“…Even though the mechanical properties may still be acceptable for many structural applications, this distortion can negatively impact high-dimensional stability composite applications where nanometer resolutions are critical. 6,7
Figure 18.Stress measurements on cured composite TC410/M55J composites after elevated heat treatment exposure to 200°C. Each specimen shows increasing curvature due to residual stress build-up based on Tg differential between tool and bag side.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferrelli and others have shown for thermosetting resins that as the degree of cure is reduced, the level of equilibrium moisture uptake is increased for equivalent humidity exposure conditions. 8,9 Stokes has shown that moisture content will impact the thermo-mechanical stresses generated within fully cured phenolic composites. 10 Therefore, a lower cure state with increased moisture content may not only result in a depressed T g , but also in a significant strain response, that ultimately may contribute to delamination failures.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the cure state of a resin may influence the moisture absorption characteristics of the composite prior to use. Ferrelli and others have shown for thermosetting resins that as the degree of cure is reduced, the level of equilibrium moisture uptake is increased for equivalent humidity exposure conditions 8,9 . Stokes has shown that moisture content will impact the thermo‐mechanical stresses generated within fully cured phenolic composites 10 .…”
Section: Introductionmentioning
confidence: 99%